RETORIKA POLITIK SUSILO BAMBANG YUDHOYONO: PENDEKATAN ANALISIS WACANA KRITIS - Fadel Mozefani; Guntur Freddy Prisanto; Niken Febrina Ernungtyas; Irwansyah Irwansyah (MEDIALOG: Jurnal Ilmu Komunikasi, 2020)
This study aims to analyze the rhetoric of the thoughts and ideas of Susilo Bambang Yudhoyono (SBY) as the sixth President of the Republic of Indonesia. Through his speech (July 24 ‘18), on YouTube, and later written on CNN online media, related to the process of forming a political party coalition that brought Prabowo Subianto as a presidential candidate in the 2019 election. The theory used in this study was qualitative-descriptive with an analytical approach critical discourse from Teun A. Van Dijk seen in dimensions; (1) text structure, (2) social cognition, and (3) social context, then associated with mass communication theory from HarollD Laswell. The results of this study are summarized with the mass communication model in form, function and meaning. The results obtained from this study create a model of mass communication with text structure (form), social cognition (function) and social context (meaning).